(untitled) - g (2013)
. : 1) . 2) . 3) . ( ) 16 . 112 56 56 . . : . . 11 11 . .
Keywords: Class Management Learning Difficulties; Cycle primaire; Elementary Education; Gestion d une classe Difficultés d'apprentissage; Iklim el Kharoub; Iklim el Kharoub